Relationship Stress Levels, Knowledge and Compliance Antenatal Care (ANC) With Preeclampsia Incidence In Pregnant Women at the West City Health Center - Arfan Walangadi; Sunarto Kadir; Ramly Abudi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Preeclampsia is a complication of pregnancy characterized by hypertension after 20 weeks of gestation accompanied by proteinuria and contributes to increased maternal morbidity. In Gorontalo City, the prevalence of preeclampsia increased from 0.71% in 2023 to 1.73% in mid-2024. Data from the West City Health Center shows that 36 out of 259 pregnant women experience preeclampsia. The purpose of analyzing the relationship between the level of stress, knowledge and compliance of Antenatal Care (ANC) and the incidence of preeclampsia in pregnant women at the West City Health Center. Quantitative research with a cross sectional study design. The population was 259 pregnant women and a sample of 72 using purposive sampling techniques. Data were collected through the Perceived Stress Scale (PSS-10) questionnaire, knowledge questionnaire, ANC compliance questionnaire and medical record data. Data analysis using the Chi-Square test. There was a significant relationship between stress levels (p = 0.000), knowledge (p = 0.017), and ANC compliance (p = 0.003) with the incidence of preeclampsia in pregnant women at the West City Health Center. The level of stress, knowledge, and compliance of ANC are factors related to the incidence of preeclampsia. Health workers are advised to optimize ANC services through early detection, ongoing education and stress level screening to prevent pregnancy complications.